Incidence, causes and outcomes of lameness cases in a working military horse population: a field study - Putnam, J.R.C.; Holmes, L.M.; Green, Martin J.; Freeman, S.L. (Wiley, 2014)
Reasons for performing study: Lameness is a common problem in the horse. Despite this, information on the incidence of lameness in horses in the UK is restricted to studies of lameness in performance horses, racehorses or referral hospital populations.